An Architecture based on Linked Data technologies for the Integration and reuse of OER in MOOCs Context - Nelson Piedra; Janneth Alexandra Chicaiza; Jorge López; Edmundo Tovar (Open Praxis, 2014)
The Linked Data initiative is considered as one of the most effective alternatives for creating global shared information spaces, it has become an interesting approach for discovering and enriching open educational resources data, as well as achieving semantic interoperability and re-use between multiple OER repositories. The notion of Linked Data refers to a set of best practices for publishing, sharing and interconnecting data in RDF format. Educational repositories managers are, in fact, realizing the potential of using Linked Data for describing, discovering, linking and publishing educational data on the Web. This work shows a data architecture based on semantic web technologies that support the inclusion of open educational materials in massive online courses. The authors focus on a type of openness: open of contents as regards alteration i.e. freedom to reuse the material, to combine it with other materials, to adapt, and to share it further under an open license.